Combined diffusion‐relaxometry microstructure imaging: Current status and future prospects. Issue 6 (19th August 2021) - Slator, Paddy J.; Palombo, Marco; Miller, Karla L.; Westin, Carl‐Fredrik; Laun, Frederik; Kim, Daeun; Haldar, Justin P.; Benjamini, Dan; Lemberskiy, Gregory; de Almeida Martins, Joao P.; Hutter, Jana
Abstract: Microstructure imaging seeks to noninvasively measure and map microscopic tissue features by pairing mathematical modeling with tailored MRI protocols. This article reviews an emerging paradigm that has the potential to provide a more detailed assessment of tissue microstructure—combined diffusion‐relaxometry imaging. Combined diffusion‐relaxometry acquisitions vary multiple MR contrast encodings—such as b‐value, gradient direction, inversion time, and echo time—in a multidimensional acquisition space. When paired with suitable analysis techniques, this enables quantification of correlations and coupling between multiple MR parameters—such as diffusivity, T 1, T 2, and T 2 ∗ . This opens the possibility of disentangling multiple tissue compartments (within voxels) that are indistinguishable with single‐contrast scans, enabling a new generation of microstructural maps with improved biological sensitivity and specificity.